THE INFLUENCE OF MARKETING STRATEGIES IN INCREASING CONSUMER ATTRACTION - Mona Enjelita Wijaya; Vicky F. Sanjaya (University of Sang Bumi Ruwa Jurai, 2022)
This study aims to examine the effect of marketing strategies in increasing consumen attractiveness at Cafe Kiyo Bandar Lampung. This research method uses a questionnaire. The sample of this study amounted to 32 respondents. The statustucal test was carried out using PLS-based Structurel Equation Modeling. Validity test using Cronbach’s Alpha Value, composite reliability and Average Variance Exstracted (AVE). Of the hypotheses proposed, there are two 3 hypotheses proposed,there are that were rejected. The conclusion of this study is the price has a positive but not significant effect on the Cafe Kiyo Bandar Lampung place. The product has a positive but not significant effect on the Cafe Kiyo Bandar Lampung , promotion has a positive and significant effect on the Cafe Kiyo Bandar Lampung.